"Because she was my first girlfriend, I didn't know any different": Making the case for mainstreaming same‐sex sex/relationship education - Donovan, Catherine; Hester, Marianne (Sex Education, 2008)
In this paper we present the case for those entering/considering same-sex relationships to be included in sex and relationship education in schools. The Government's Guidance on Sex and Relationship Education provides a rationale for including same-sex relationships when it says that schools should meet the needs of all their pupils "whatever their developing sexuality." Research on sex education and domestic violence prevention for schools has highlighted issues of gender, power, the importance of understanding context in providing skills and knowledge for safer sex and non-abusive relationships. However, both tend to assume the context is heterosexuality. Results from our Economic & Social Research Council-funded study of domestic violence in same-sex and heterosexual relationships indicates that those aged under 25 years of age and those in first same-sex relationships are particularly vulnerable to experiencing domestic violence. Four themes arise from the qualitative data that provide a rationale for the provision of sex and relationship education to these young people: first same-sex relationships as an affirmation of identity; and lack of knowledge about what to expect in same-sex relationships; of embeddedness in lesbian, gay, bisexual, transgender and queer friendship networks; and of resources to seek help.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; approches et analyses; discours dominant; genre; hétérosexisme; identités LGBTQIA2+; inégalités; périodes historiques; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; violences; violences conjugales; éducation sexuelle; étude qualitative

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales